Intrauterine growth restriction: etiology associated with maternal and placental causes (Research, Society and Development, 2022)
Intrauterine Growth Restriction (IUU) is an important complication of pregnancy due to high rates of perinatal morbidity and mortality. This complication is defined as a fetus that cannot reach its growth percentage, caused by maternal and placental factors. Thus, this study aimed to evaluate maternal and placental determinants, as well as to specify diagnostic methods and possible outcomes in the face of IUD. A literature review was conducted in the PubMed, SCIELO and VHL databases, having as inclusion criteria: articles published in the period from 2010 to 2022 in the language in Portuguese and English. 16 publications eligible for inclusion in this review were found. In view of the analysis of the literature, it was noted that there are several determinants of IUR, such as: age, nutritional status, hypertension, chronic kidney disease, diabetes, illicit drug use, tobacco, ethnicity, anemia, abnormal implantation of the placenta, single umbilical artery, placenta previa, uterine abnormalities, circumvalized placenta, placental infarctions and others. To identify the fetus with this delay, the measurement of uterine height (AU), obstetric ultrasound, fetal weight estimation (PEE) and umbilical artery Doppler are used. As for the possible results in this pathology, it can lead to probable complications for the newborn and in childhood, consistent with changes in health condition. Thus, it is concluded that there are multiple factors related to IUEd and that the identification of the main changes involved by diagnostic methods is of fundamental importance to avoid problems in the health of the fetus and pregnant women.